Familial geopolitics and ontological security: intergenerational relations, migration and minority youth (in)securities in Scotland. Issue 5 (19th October 2020) - Botterill, Kate; Hopkins, Peter; Sanghera, Gurchathen
ABSTRACT: This paper discusses the family as a site of geopolitics. Bridging scholarship in feminist geopolitics, political psychology and sociology, we explore the psycho-social dynamics of family life and theorise the family as a multi-scalar, relational site of security. Original data collected with ethnic and religious minority youth in Scotland are presented alongside an analysis of how family relations, at interconnected scales, mitigate against and/or re-inscribe broad geopolitical narratives of security. We employ the concept of ontological security (OS) to analyse the role of the family, and the relationships within it, on shaping youth securities. We discuss (1) how family histories and intergenerational experience shape young people's sense of security; (2) how young people negotiate and resist family norms and values that reproduce securitizing geopolitical narratives; and (3) how young people find security when family is absent or indeterminate. In each case, we analyse how geopolitics operates through family life. The paper makes two key contributions: first, we use original empirical data to theorise ethnic and religious minority youth securities; second, we show the value of OS as a conceptual tool for understanding psycho-social dimensions of familial geopolitics.